EFFECT OF STARVATION ON THE BIOCHEMICAL COMPOSITION OF CLARIAS BATRACHUS(LINN.) - BANO, MISS YAGANA (Fishery Technology, 2017)
Marked changes were observed in different chemical constituentsof Clarias batrachus during starvation. The nitrogenand protein fractions showed a definite pattern of variations.The highest values of these were recorded on lOth day ofstarvation and thereafter values declined gradually. On theother hand, the acid soluble phosphorus exhibited a reversetrend, increasing graduaUy from the first to the 30th day ofstarvation. These changes have been attributed mainly to theenergy and metabolic demands of the starving fish.